Big Bend's Ancient and Modern Past - Mallouf, Robert J.; Glasrud, Bruce A. (Book collections on Project MUSE., 2013)
The Big Bend region of Texas - variously referred to as "El Despoblado" (the uninhabited land), "a land of contrasts," "Texas' last frontier," or simply as part of the Trans-Pecos - enjoys a long, colorful, and eventful history, a history that began before written records were maintained. This book provides a helpful compilation of articles originally published in the Journal of Big Bend Studies, reviewing the unique past of the Big Bend area from the earliest habitation to 1900.